Acute Gastric Necrosis in a Fourteen-Year Old Child - Joshi, Pravin Kumar (Asian Journal of Medical Sciences, 2013)
Acute gastric necrosis is a rare entity of several possible causes. Progression of the disease is usually fulminant and diagnosis is made during surgery only. A-14 year child with acute onset abdominal pain and vomiting and with features of shock presented to the hospital. Rapid progression of surgical abdomen, hemorrhagic drainage in nasogastric tube and presence of gas in the portal vein could be a strong indicator of gastric necrosis. Recognizing the risk factors and prompt surgical intervention is the key to management. Asian Journal of Medical Science, Volume-4 (2013), Pages 44-48 DOI: http://dx.doi.org/10.3126/ajms.v4i4.8083